A comprehensive review of prognostic scoring systems to predict survival after transjugular intrahepatic portosystemic shunt placement. Issue 2 (30th September 2022) - Yang, Chongtu; Xiong, Bin
Abstract: Patient prognosis after transjugular intrahepatic portosystemic shunt (TIPS) placement is relatively poor and highly heterogeneous; therefore, a prognostic scoring system is essential for survival prediction and risk stratification. Conventional scores include the Child–Turcotte–Pugh (CTP) and model for end‐stage liver disease (MELD) scores. The CTP score was created empirically and displayed a high correlation with post‐TIPS survival. However, the inclusion of subjective parameters and the use of discrete cut‐offs limit its utility. The advantages of the MELD score include its statistical validation and objective and readily available predictors that contribute to its broad application in clinical practice to predict post‐TIPS outcomes. In addition, multiple modifications of the MELD score, by incorporating additional predictors (e.g., MELD‐Sodium and MELD‐Sarcopenia scores), adjusting coefficients (recalibrated MELD score), or combined (MELD 3.0), have been proposed to improve the prognostic ability of the standard MELD score. Despite several updates to conventional scores, a prognostic score has been proposed (based on contemporary data) specifically for outcome prediction after TIPS placement. However, this novel score (the Freiburg index of post‐TIPS survival, FIPS) exhibited inconsistent discrimination in external validation studies, and its superiority over conventional scores remains undetermined. Additionally, several tools display potential for application in specific TIPS indications (e.g., bilirubin‐platelet grade for refractory ascites), and biomarkers of systemic inflammation, nutritional status, liver disease progression, and cardiac decompensation may provide additional value, but require further validation. Future studies should consider the effect of TIPS placement when exploring predictors, as TIPS is a pathophysiological approach that substantially alters systemic hemodynamics and ameliorates bacterial translocation and malnutrition. Abstract : Prognostic tools for survival prediction and risk stratification after transjugular intrahepatic portosystemic shunt placement. Key points: Multiple prognostic scores have been applied to predict post‐transjugular intrahepatic portosystemic shunt (TIPS) survival, including conventional scores (e.g., Child–Turcotte–Pugh, a model for end‐stage liver disease [MELD] and MELD‐sodium scores) and scores based on contemporary data (e.g., MELD 3.0 and Freiburg index of post‐TIPS survival score). Novel prognostic biomarkers, especially those of systemic inflammation, nutritional status, liver disease severity, and cardiac decompensation could provide additional prognostic value for existing scoring systems.